Lund University Biological Museum - Botanical collection (LD) - Håkan Wittzell (Lund University, 2010)
The scientific collections of Lund Universty Botanical Museum (Herbarium LD) comprise 2.5 million specimens divided into algae & cyanobacteria (102 000), bryophytes (149 000), fungi (63 000), lichens (170 000) and vascular plants (2 000 000). The collections go back to the 18th century and represent more than 250 years of scientific research. Coverage is worldwide with particularly important collections from Sweden, Denmark, Norway, Finland, Greece, Turkey, North Africa, South Africa, Zimbabwe and Australia.
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi